2020
DOI: 10.3390/nu12061772
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Status in Adherent and Non-Adherent Patients with Phenylketonuria: A Cross-Sectional Study

Abstract: This is the first study to evaluate vitamin K status in relation to dietary intake and phenylalanine dietary compliance in patients with phenylketonuria (PKU). The dietary and PKU formula intake of vitamin K was calculated in 34 PKU patients, with vitamin K status determined by the measurement of prothrombin induced by vitamin K absence (PIVKA-II). Blood phenylalanine concentrations in the preceding 12 months were considered. There were significantly more phenylalanine results exceeding 6 mg/dL in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our results significantly contradict the findings by Oztürk et al [10], who found five times more frequent HP infection in individuals with PKU with worse metabolic control than in those with better metabolic control (subjects with a median concentration higher or lower than 600 mmol/L, respectively) in their study. PKU diet compliance definitely influences neurological impairment and may impact nutritional status [22]. However, it is difficult to find a link to a potentially higher prevalence of HP in patients with PKU that are not significantly intellectually impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Our results significantly contradict the findings by Oztürk et al [10], who found five times more frequent HP infection in individuals with PKU with worse metabolic control than in those with better metabolic control (subjects with a median concentration higher or lower than 600 mmol/L, respectively) in their study. PKU diet compliance definitely influences neurological impairment and may impact nutritional status [22]. However, it is difficult to find a link to a potentially higher prevalence of HP in patients with PKU that are not significantly intellectually impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the sensitivity analysis are shown in Figure S10, and the results of cumulative analysis are presented in Figure S11. The exclusion of studies considered to have a high risk of bias did not alter the findings 1 -mean ± standard deviation; 2 -patients under diet treatment; 3 -patients who discontinued the protein substitution at 18 years of age; 4 -serum; 5 -folic acid; 6 -ng/mL; 7 -data were received from authors; 8 -25(OH)D; 9 -pg/mL; 10 -all PKU patients; 11 -patients with high adherence; 12 -patients with low adherence; 13 -nmol/L; 14 -median (min-max); 15 -pmol/L; 16 -mean ± standard error of the mean; 17 -cholecalciferol; 18 -µmol/L; 19 -patients followed a Phe-restrictive diet in childhood and stopped it at the average age of 6 years; 20 -plasma; 21 -well-controlled; 22 -poorly controlled; 23 -patients exclusively received phenylalanine-restricted diets; after the age of 20 years, restrictions of phenylalanine differed greatly among patients; 24 -25(OH)D3; 25 -patients with phenylalanine levels in the blood kept within the recommended values; 26 -until the age of 15 years, patients received phenylalanine-restricted diets with phenylalanine-free milk; thereafter, the restrictions of phenylalanine varied among the patients; 27 -female participants; 28 -male participants; 29 -data presented in nmol/g prot; 30 -27 had acceptable dietary control and 15 had poor dietary compliance; 31 -patients were requested to discontinue their vitamin supplementation for 30 days before the study; 32 -red blood cells folate; 33 -median (interquartile range); 34 -phenylalanine tolerance < 12 mg phenylalanine•kg −1 •d −1 ; 35 -phenylalanine tolerance > 12 mg phenylalanine•kg −1 •d −1 ); 36 -strict diet; 37 -relaxed diet; 38 -µg/L; 39 -no info about measurement material; 40 -ng/L; 41 -erythrocyte tocopherol;…”
Section: Comparison Of Vitamin D Levelsmentioning
confidence: 99%
“…PKU patients may be at risk of developing deficiencies in various nutrients, including vitamins D [17,18], B12 [19][20][21][22], K [23], as well as zinc and selenium [22,24]. Vitamins play pivotal roles in various physiological processes, and any disturbances in their levels may have significant implications for overall health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation